Exploring the effects of documentation on socio-economic experiences of Zimbabwean migrant workers in South Africa - Ndlovu, Performance (My University, 2018)
In response to migration trends, South Africa has been adopting the special permits programme as a form of documentation to meet the growing migrant populace. However, little is known regarding Zimbabwe Special Permit programme (ZSP), the impact. The focus of this study was therefore exploring the effects of documentation on the socio-economic experiences of Zimbabwean migrant workers in South Africa. These lived experiences were explored through a qualitative study with 15 low skilled ZSP holders, living in Hillbrow, Johannesburg. The study finds that documentation does not also always correspond with better livelihoods or improved social and economic well-being. Indeed, it is important to note that the presence of an empowering legal policy such as the ZSP does not automatically translate to better access to services. Even with state-granted rights, migrants usually struggle to convert their legal status into effective claims to services (Landau, 2010) as some other factors come into play that influence the effects of documentation on an aspect such as migrants socio-economic welfare. These include profile of holders, the host country, society, service providers etc. Further, the study finds that lack of legal status also does not necessarily generate the forms of social suffering and economic hardships delineated in some cases. Indeed, findings from this comparative study (pre-post ZSP) show socio-economic experiences of migrant workers where they have access to jobs, education, and employment rights though they might be on the surface this is not as a result of documentation being the key issue but rather other dominating factors. Therefore the study shows that both outcomes are possible (positive and negative). By challenging some of the scholarly conclusions and public assumptions about the effect of documentation on the socio-economic wellbeing of migrants in their host societies, these findings contribute to ongoing theoretical and empirical debates in this regard.
A research report submitted in partial fulfillment of the requirements for the degree of MA: Migration and Displacement Studies at University of the Witwatersrand, 2018